2015
DOI: 10.1007/s12094-015-1341-8
|View full text |Cite
|
Sign up to set email alerts
|

Patients with brain metastases derived from gastrointestinal cancer: clinical characteristics and prognostic factors

Abstract: RPA class, chemotherapy after brain metastases, and treatment regimens were independent prognostic factors for the survival of patients with brain metastases derived from gastrointestinal cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 23 publications
3
16
0
Order By: Relevance
“…Our study showed that the survival time for patients without local treatment for brain metastases was 1.97 months, which was similar to that of reports in literature [10, 27]. Median survival time for the entire cohort was 10.25 months, which seemed to be longer than that reported previously (usually within 7 months) [8, 10, 18, 25, 27]. This may be a result of better patient awareness of symptoms and the application of screening programs leading to earlier diagnosis, effective systemic therapies, and aggressive local therapy.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our study showed that the survival time for patients without local treatment for brain metastases was 1.97 months, which was similar to that of reports in literature [10, 27]. Median survival time for the entire cohort was 10.25 months, which seemed to be longer than that reported previously (usually within 7 months) [8, 10, 18, 25, 27]. This may be a result of better patient awareness of symptoms and the application of screening programs leading to earlier diagnosis, effective systemic therapies, and aggressive local therapy.…”
Section: Discussionsupporting
confidence: 91%
“…The majority of patients (76.3%) developed BM more than 30 days after the primary tumor diagnosis. 194 patients (71.9%) had extracranial metastases, and similar observations were described by other authors [2527]. Data further showed that only 26.3% patients had multiple cerebral lesions (more than 3), which was different from lung cancer [1].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The number of patients with brain metastases has gradually risen in recent years. Moreover, brain metastasis has been observed in advanced gastric cancer, with a poor prognosis (median survival of 2‐4 months) . However, this patient survived for 2 years while receiving apatinib.…”
Section: Discussionmentioning
confidence: 97%
“…However, the incidence of brain metastases in GI malignancies is low, ranging from 0.33% with pancreatic cancer to 4% in colorectal cancer and imaging for brain metastases is primarily guided by clinical suspicion and symptoms. [72][73][74] Although there is a lack of prospective or retrospective data evaluating CDT and PCDT specifically in GI malignancies, several factors are important to consider when evaluating a patient for CDT or PCDT. Patients with GI malignancies are at higher risk of bleeding with anticoagulation, 14 thus, careful consideration and patient selection is warranted to prevent significant bleeding complications that can occur with overnight infusion of thrombolytics.…”
Section: Catheter-directed Thrombolysismentioning
confidence: 99%